Cardiorespiratory fitness and body fat distribution in women with 50 years or more - Freitas Júnior, Ismael Forte; Rosa, Clara Suemi da Costa; Codogno, Jamile Sanches; Bueno, Denise Rodrigues; Buonani, Camila; Conterato, Igor; Fernandes, Rômulo Araújo; Converso, Maria Estelita Rojas; Gomes, Jaime de Oliveira (Revista da Escola de Enfermagem da USP, 2010)
To verify the relationship between cardiorespiratory fitness and body fat in women. Evaluations were performed on 229 women with ages ranging between 50 and 84 years. Anthropometric assessment was performed and waist/hip ratio and conicity index values were obtained. The cardiorespiratory fitness was evaluated by the six minutes walk test and one pedometer was used to evaluate the speed, length, and total number of steps. The results were distributed in quartile, and interquartil comparison was performed by means of analysis of variance with post-hoc test. The relationship between the six minutes walk test and anthropometrics was identified using the Pearson's correlation coefficient. Results showed that women with cardiorespiratory fitness in the quartile4 were younger than those in quartile1 (p